LAPORAN KASUS: TRANSFORMASI ERITRODERMA PSORIATIKA MENJADI LIMFOMA SEL T-KUTAN - Ismiralda Oke Putranti; Amelia B Rahardjo; Citra Primanita; Lilik Karsono; Arundito Widikusumo (Medical and Health Journal, 2023)
Background: Erythrodermic psoriasis (EP) is a severe type of psoriasis, a chronic inflammatory disease characterized by general erythematous condition with thick scale all around the body. The treatment of EP consists systemic medications like cyclosporine or methotrexate and biologic agents, which lately suggested related to the development of cutaneous T-cell lymphoma (CTCL) in severe psoriasis patients. Case Report: A 45-year old, Javanese male was diagnosed previously with EP that transformed to CTCL. His previous history, he was histologically confirmed as psoriasis vulgaris since 2014 and was treated regularly with methotrexate. After 5 years, he gradually suffered several episodes of erythrodermic condition and was diagnosed with erythrodermic psoriasis with unusual pruritic hyperkeratotic plaques and ulcers on his trunks without any general lymph nodes enlargement. Peripheral blood smear showed Sezary cell and histopathology result confirmed CTCL. He was treated with combination of radiotherapy, phototherapy and topical regiments with a good result and acceptable. Discussion: Several studies suggested that severe psoriasis had increased the susceptibility of CTCL, especially with the use of cyclosporine, methotrexate or biologic agents as the treatment. In this case, methotrexate might play role in the development of CTCL or enhanced the transformation of EP to CTCL. Combination of localized radiation therapy, NBUVB and topical therapy gave a quiet good result for the skin condition and increased patient’s quality of life. Conclusion: Erythrodermic psoriasis might transform or develop to CTCL which in this case was probably related to the use of methotrexate.